Survival and metamorphosis rate of swimming crab Portunus pelagicus larvae with the use of phytoecdysteroid in the artificial feed - Nikhlani, Andi; Sukarti, Komsanah (Indonesian Society of Scientific Aquaculture (ISSA), 2017)
ABSTRACT The survival rate of blue swimming crabs and the larval metamorphosis processes are still low in hatcheries. The objective of this study was to evaluate the effects of different phytoecdysteroids doses on both the survival and the rate of Blue swimmer crab larvae metamorphosis. The study consisted of four different phytoecdysteroids treatments, namely: control (0 mg/100 g of feed), 1 mg/100 g of feed, 2 mg/100 g of feed, and 4 mg/100 g of feed. Each treatment was replicated three times. The survival rate of the larvae was analyzed through analysis of variance, while the rate of larval metamorphosis was descriptively analyzed. The results showed that the dose of phytoecdysteroid of 2 mg/100 g of artificial feed resulted in the highest survival and the fastest metamorphosis speed of crab larvae for zoea-2 and zoea-3, and the dose of 4 mg/100 g of artificial feed for stadia megalopa and crablet. Keywords: phytoecdysteroids, survival rate, metamorphosis, blue swimming crab ABSTRAK Kelangsungan hidup rajungan dalam pembenihan masih rendah, dan proses metamorfosis larva masih lambat. Tujuan penelitian ini adalah untuk mengevaluasi pengaruh pemberian fitoekdisteroid dosis berbeda terhadap kelangsungan hidup dan kecepatan metamorfosis larva rajungan. Penelitian ini terdiri atas empat perlakuan dosis fitoekdisteroid yang berbeda, yaitu: kontrol (0 mg/100 g pakan), 1 mg/100 g pakan, 2 mg/100 g pakan, dan 4 mg/100 g pakan dengan masing-masing perlakuan dilakukan tiga kali ulangan. Kelangsungan hidup larva dianalisis menggunakan analisis sidik ragam, sedangkan kecepatan metamorfosis larva dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa dosis fitoekdisteroid sebanyak 2 mg/100 g pakan buatan menghasilkan kelangsungan hidup tertinggi dan proses metamorfosis larva rajungan tercepat untuk stadia zoea-2 dan zoea-3, serta dosis 4 mg/100 g pakan buatan untuk stadia megalopa dan crablet. Kata kunci: fitoekdisteroid, kelangsungan hidup, metamorfosis, rajungan